Pelaksanaan Dirasah Qur’aniyah sebagai Upaya Peningkatan Kualitas Baca Al-Qur’an di Desa Tukamasea Kabupaten Maros - Iskandar Iskandar; M Amirullah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Tukamase Village is one of the villages where STIBA Makassar Community Service Program (KKN) III students are placed, in Bantimurung District, Maros Regency. All people of Tukamase village are Muslims of various ages, ranging from children to the elderly people, so the planned activity program was directed to people of various backgrounds. Among the programs formulated by STIBA Makassar Community Service Program (KKN) III students were programs of the Koran discourse. The purpose of this program was to enhance the competence and understanding of reading the Koran properly. The details of Koran discourse consisted of: (1) basic Koran learning at TKA/TPA; (2) dirosa; (3) enhancement of recitation; (4) discourse of history of the Prophet; (5) discourse of Koran interpretation; (6) language discourse (Arabic); (7) Koran donation. Most people of Tukamase before participating in the Koran discourse programs had minimum competence and quality of understanding Koran, such as being unable to read the Koran fluently, not understanding the rules of recitation, and even among participants were those who were illiterate in the Koran, and after participating in the activities in Koran discourse, people of Tukamase had developed in terms of competence and quality of understanding the Koran, especially in terms of pronunciation of the letters and reading the Koran according to the rules of recitation. In addition, Koran discourse program also provided a positive influence in fostering the intensity of Muslim community at Tukamase village’s interaction with the Koran.